Pengembangan Media Papan Huruf Geser Pada Keterampilan Membaca Permulaan Kelas 1 Tema 3 Subtema 1 Di SDN 044845 Payanderket - Triana Ocieli Putri Br Karo; Erlinda Simanungkalit; Nurmayani Nurmayani; Apiek Gandamana; Winara Winara (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
This study aims to design, develop, and test the feasibility, practicality and effectiveness of papan huruf geser media in the early reading skills of class I theme 3 sub-theme 1 at SDN 044845 Payanderket in Indonesian. The problem in this study is that the learning media used in reading activities are inadequate, the learning methods used in reading activities are less varied and students do not play an active role in the learning process. Researchers use development research (Research and Development) according to Thiagarajan, namely the 4D model (Define, Design, Development, Dessemination). The subjects in this research were class I students at SDN 044845 Payanderket and the research object was the papan huruf geser media. Data collection techniques use questionnaires and learning outcomes tests. The results of the media validation test for media experts obtained a percentage of 98.21% in the